2010
DOI: 10.1016/j.jcf.2010.06.001
|View full text |Cite
|
Sign up to set email alerts
|

A high frequency of the Cystic Fibrosis 2184insA mutation in Western Ukraine: Genotype–phenotype correlations, relevance for newborn screening and genetic testing

Abstract: We present the first comprehensive report on the distribution and genotype-phenotype correlations of CF-causing mutations in Western Ukraine (former Galicia). The 2184insA mutation was identified in 17 unrelated CF patients, 2 of whom are homozygotes for this allele. This mutation is associated with the classical form of CF. The high frequency of 2184insA mutation (7.20% of all mutated CF chromosomes) suggests that it is likely of Galician origin, from where it has spread throughout Europe and beyond. The achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 8 publications
5
18
0
Order By: Relevance
“…), this result shows population relatedness of both regions given their close longterm historical ties. Therefore, our data confirm the "Galician origin" of this mutation [18] given its decreasing gradient towards the region from which our patients were drawn. It will be of interest to study similar cohorts of CF patients in neighboring Eastern Slovakia, Southeastern Poland, Belarus and Northwestern Romania in order to further substantiate this likely regional founder effect.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…), this result shows population relatedness of both regions given their close longterm historical ties. Therefore, our data confirm the "Galician origin" of this mutation [18] given its decreasing gradient towards the region from which our patients were drawn. It will be of interest to study similar cohorts of CF patients in neighboring Eastern Slovakia, Southeastern Poland, Belarus and Northwestern Romania in order to further substantiate this likely regional founder effect.…”
Section: Discussionsupporting
confidence: 81%
“…In this regard a recent paper of Makukh et al (2010) [18] reported that this allele is the second most common mutation in Western Ukraine, comprising 7.20% of all mutated CF alleles. Since Western Ukraine is bordering the area from which our cohort was drawn (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…It is localized in exon 14 of the CFTR gene in the polyA tract where, more commonly, at least in the Italian population, the deletion of 1 or 2 nucleotides determining the c.2052delA (2184delA) mutation is observed. In studies conducted in populations of Eastern European countries (Ukraine, Hungary, Poland, and Slovakia), the 2184insA mutation was reported as a severe mutation, an assumption that is in line also with our findings [15,16]. In fact, regardless of the second allele, all our patients showed PI; nevertheless, only 1 case was identified from the neonatal screening.…”
Section: Discussionsupporting
confidence: 91%
“…The exonic 2184insA mutation in addition to others (eg, CFTRdele2,3, 3849 þ 10kbC4T ) occurs more frequently in Central and Eastern Europe. 29 Thus, the main reason for the application of our strategy was the diversity of mutations in the Polish population, for which commercial tests are not suited (Tables 2 and 3). An extended molecular analysis revealed that 3600 þ 2insT, mutations in loci 1898 þ 1 (G4C or G4A) were detected in two and three cases of CF children with extended analysis (thus4cut off 0.45% of mutated alleles detected in NBS CF).…”
Section: Discussionmentioning
confidence: 99%